ANALISIS YURIDIS TERHADAP PERLINDUNGAN KONSUMEN DALAM PEREDARAN SKINCARE PALSU DI TOKO ONLINE BERDASARKAN UU NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Pelawi, Mesikel; Bagaskara P., Ketut Krisna Hari; Dantes, Komang Febrinayanti (Jurnal Ilmu Hukum Sui Generis, 2025)
Online transactions, including in the cosmetics industry, have been driven by advances in information technology. However, this convenience has been accompanied by an increase in the circulation of counterfeit skincare products in online stores, which can harm consumers financially and health-wise. The purpose of this study is to examine how Law No. 8 of 1999 on Consumer Protection (UUPK) provides legal protection for consumers against the circulation of counterfeit cosmetics in online stores. Additionally, this study also seeks to identify ambiguities and issues in its implementation. This study uses a normative legal method employing case studies and a legislative approach. Data was obtained by reviewing literature, examining legal regulations, and analyzing case documentation. The study reveals that legal protection for customers purchasing counterfeit skincare products on online stores is not yet optimal. This is attributed to insufficient oversight, lack of clear regulations regarding market responsibility, and low consumer awareness of their rights. Additionally, the complaint and dispute resolution system still does not adequately protect consumers. To provide better consumer protection in the digital age, this study recommends strengthening regulations, further oversight by relevant agencies, improving consumer education, and refining the complaint and enforcement systems.